Identification of a novel nucleophosmin‐interaction motif in the tumor suppressor p14arf. (15th January 2018) - Luchinat, Enrico; Chiarella, Sara; Franceschini, Mimma; Di Matteo, Adele; Brunori, Maurizio; Banci, Lucia; Federici, Luca
Abstract : The tumor suppressor p14arf interacts, in response to oncogenic signals, with the p53 E3‐ubiquitin ligase HDM2, thereby resulting in p53 stabilization and activation. In addition, it also exerts tumor‐suppressive functions in p53‐independent contexts. The activities of p14arf are regulated by the nucleolar chaperone nucleophosmin (NPM1), which controls its levels and cellular localization. In acute myeloid leukemia with mutations in the NPM1 gene, mutated NPM1 aberrantly translocates in the cytosol carrying with itself p14arf that is subsequently degraded, thus impairing the p14arf‐HDM2‐p53 axis. In this work we investigated the complex between these two proteins by means of NMR and other techniques. We identified a novel NPM1‐interacting motif in the C‐terminal region of p14arf, which corresponds to its predicted nucleolar localization signal. This motif recognizes a specific region of the NPM1 N‐terminal domain and, upon binding, the two proteins form soluble high molecular weight complexes. By NMR, we identified critical residues on both proteins involved in the interaction. Collectively, our data provide a structural framework to rationalize the overall assembly of the p14arf‐NPM1 supramolecular complexes. A number of p14arf cancer‐associated mutations cluster in this motif and their effect on the interaction with NPM1 was also analyzed. Abstract : The nucleolar chaperone nucleophosmin (NPM1) controls the activity and cellular localization of the p14arf tumour suppressor. In acute myeloid leukemia cells with mutations in the NPM1 gene, p14arf is aberrantly transported to the cytosol by mutant NPM1, where it is degraded. In this report, Banci, Federici and colleagues use NMR and other approaches to provide new insight into the interaction between NPM1 and p14arf, identifying a new NPM1‐interacting motif in p14arf. These data clarify the mechanism by which NPM1‐p14arf supramolecular complexes assemble, and define how cancer‐linked mutations in NPM1 and p14arf affect these interactions.